Does size asymmetry exacerbate the inefficiency of tax competition? - Yutao Han; Patrice Pieretti; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2013)
Many authors demonstrate that the tax gap resulting from tax competition increases with the size asymmetry of the competing countries. Consequently, increasing country-size disparities exacerbates the inefficiency of tax competition.The aim of this note is to show that this classical view has no general validity if we consider that countries compete not only in taxes but also in the provision of infrastructure. The simple model we develop for this purpose demonstrates that the effect of size disparity on efficiency depends crucially on the degree of international capital mobility.
Keywords: H21; H73; F21; 330; tax competition; social welfare; inefficiency; infrastructure